3D QSAR ANALYSIS ON OXADIAZOLE DERIVATIVES AS ANTICANCER AGENTS (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Three dimensional quantitative structure activity relationship (3D QSAR) study by means of partial least square regression (PLSR) method was performed on a series of 3-(Aryl)-N-(Aryl)-1, 2, 4-Oxadiazol-5-amines as antiproliferative agents using molecular design suite (VLifeMDS). This study was performed with 20 compounds (data set) using sphere exclusion (SE) algorithm and manual selection method used for the division of the data set into training and test set. PLSR methodology with stepwise (SW) forward-backward variable selection method was used for building the QSAR models. Five predictive models were generated with sphere exclusion and two with manual data selection methods using PLSR. The most significant model is having correlation coefficient 0.9334 (squared correlation coefficient r2 = 0.8713) indicating noteworthy correlation between biological activity and descriptors. The model has internal predictivity 74.45% (q2 = 0.7445) and highest external predictivity 81.09 % (pred_r2 = 0.8109) and lowest error term for predictive correlation coefficient (pred_r2se = 0.1321). Model showed that steric (S_1278, S_751) and electrostatic (E_307) interactions play important role in determining antiproliferative activity. The molecular field analysis (MFA) contour plots provided further understanding of the relationship between structural features of substituted oxadiazole derivatives and their activities which should be applicable to design newer potential antiproliferative agents.